2020
DOI: 10.1111/febs.15465
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic ATPase activity of Mycobacterium tuberculosis UvrC is crucial for its damage‐specific DNA incision function

Abstract: The nucleotide excision repair pathway is essential for the removal of bulky DNA adducts generated by exogenous chemicals, UV radiation and by‐products of cellular metabolism. In bacteria, the UvrAB complex recognizes and binds to the DNA adducts, and UvrC catalyses the dual incision of the damaged strand. Here, we reveal that Mycobacterium tuberculosis UvrC possesses an intrinsic ATPase activity, which is essential for the incision of the damaged DNA strand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 67 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…2 and with the prokaryotic pattern of dual incisions 7 nucleotides 5' and 3-4 nucleotides 3' to the Pyr-Pyr. A different set of incision sites were described for M. tuberculosis repair, likely due to the use of indirect evidence for the 3' incision site and the absence of UvrA and UvrB in repair reactions in appropriate amounts (19).…”
Section: Smegmatis Removes Cyclobutane Pyrimidine Dimers From the mentioning
confidence: 99%
See 1 more Smart Citation
“…2 and with the prokaryotic pattern of dual incisions 7 nucleotides 5' and 3-4 nucleotides 3' to the Pyr-Pyr. A different set of incision sites were described for M. tuberculosis repair, likely due to the use of indirect evidence for the 3' incision site and the absence of UvrA and UvrB in repair reactions in appropriate amounts (19).…”
Section: Smegmatis Removes Cyclobutane Pyrimidine Dimers From the mentioning
confidence: 99%
“…Against this background, then, it was rather unexpected when it was recently reported that in Mycobacterium tuberculosis (which possess the UvrA, B, and C homologs), the UvrC protein alone was capable of making dual incisions bracketing a bulky adduct 15 nucleotides 3' and 9 nucleotides 5' flanking the damage to generate a 25-mer, and it was concluded that dual incisions made by uvrC in M. tuberculosis are analogous to those made by its orthologs in yeast and humans (19). In light of this report, we decided to investigate dual incisions in Mycobacteria using M. smegmatis as representative of the genus.…”
mentioning
confidence: 99%
“…UvrC is an enzyme possessing a dual endonuclease activity catalyzed by two independent endonuclease domains: one located at its N-terminus that is responsible for the 3′ incision and another located at its C-terminus that is in charge of the 5′ incision ( 1–3 , 23–26 ). Mycobacterium tuberculosis UvrC (MtUvrC) has additionally been shown to possess an intrinsic DNA-independent ATPase activity ( 27 ). Crystal structures of the two catalytic domains of Thermatoga maritima UvrC (TmUvrC) have been determined.…”
Section: Introductionmentioning
confidence: 99%